2012
DOI: 10.1556/jfc-d-12-00006
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Silica Capsules: Taming the Reactivity of SiCl4 Using Flow and Chemistry

Abstract: Monodisperse silica microcapsules are typically fabricated using hard templating methods. Though soft templating methods are known, none yet provides a fast and easy method to produce monodisperse capsules. Herein, we describe a mesofluidic strategy whereby monodisperse droplets of reactive silica precursors are formed using a snap-off mechanism via a T junction. Both the mesofluidic system and the composition of the reactive silica formulation are critical features. Using solid-and solution-state 29 Si nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Indeed, solution-phase 29 Si nuclear magnetic resonance (NMR) spectroscopy confirmed that rapid exchange of chloride and ethoxy groups occurred between TEOS and SiCl 4 within 10 min after the preparation of the disperse-phase solution ( Figure S1). This is even faster than in our previous report of purely silica microparticles that did not use titanium alkoxides [26].…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Indeed, solution-phase 29 Si nuclear magnetic resonance (NMR) spectroscopy confirmed that rapid exchange of chloride and ethoxy groups occurred between TEOS and SiCl 4 within 10 min after the preparation of the disperse-phase solution ( Figure S1). This is even faster than in our previous report of purely silica microparticles that did not use titanium alkoxides [26].…”
Section: Resultsmentioning
confidence: 57%
“…Synthesis of Mixed Silica-Titania Shells via Interfacial Condensation. Previous work in our laboratory demonstrated that fast-reacting precursors such as SiCl 4 could be used to create microcapsules by tuning the condensation rate using alcohol additives [26]. Formation of HCl gas upon fast hydrolysis of the Si-Cl bonds served to create the void around which the interfacial polymerization proceeded, leaving behind the inorganic shell.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations